Use of loaded conditioning activities to potentiate middle- and long-distance performance: A narrative review and practical applications - Blagrove, R. C.; Howatson, G.; Hayes, P. R. (The Journal of Strength and Conditioning Research, 2019)
The warm-up is an integral component of a middle- and long-distance athlete's preperformance routine. The use of a loaded conditioning activity (LCA), which elicits a postactivation potentiation (PAP) response to acutely enhance explosive power performance, is well researched. A similar approach incorporated into the warm-up of a middle- or long-distance athlete potentially provides a novel strategy to augment performance. Mechanisms that underpin a PAP response, relating to acute adjustments within the neuromuscular system, should theoretically improve middle- and long-distance performance through improvements in submaximal force-generating ability. Attempts to enhance middle- and long-distance-related outcomes using an LCA have been used in several recent studies. Results suggest that benefits to performance may exist in well-trained middle- and long-distance athletes by including high-intensity resistance training (1-5 repetition maximum) or adding load to the sport skill itself during the latter part of warm-ups. Early stages of performance seem to benefit most, and it is likely that recovery (5-10 minutes) also plays an important role after an LCA. Future research should consider how priming activity, designed to enhance the VO2 kinetic response, and an LCA may interact to affect performance, and how different LCAs might benefit various modes and durations of middle- and long-distance exercises.